An Integrated Approach to Teach Communication Skills Using Educational Technologies - Shannon Arnold; Suzi Taylor (Journal of Applied Communications, 2013)
The purpose of this pre-experimental pre-test/post-test design was to identify a group of agricultural education students’ knowledge and perceptions towards the use of integrated educational technologies in the classroom. The population was 17 agricultural education students enrolled in an agricultural communications course over a two-year period. A multimedia content development touch screen resource was integrated into the course as a capstone project. Pretest and posttest evaluations showed 6% to 57% changes in knowledge as a result of the digital capstone project. The most significant changes were seen in storyboarding, multimedia project development, and graphic design principles, indicating that students require additional education in these areas. The lowest percentage changes were seen in the same three competencies each year; revealing that students were most knowledgeable in interviewing, technical writing, and giving public presentations. The findings revealed that students gained the most knowledge in technology development, integration and application, rather than interpersonal skill building. This integrated course provides an example of how educators can design courses that not only increase students’ communications knowledge and skills, but also gain realistic experience by creating their own multimedia content for public communication.
Keywords: communication skills; educational technologies; multimedia; agricultural education students; integrated learning